Pengembangan Film Pembelajaran Musim Penghujan Pada Tema Peristiwa Alam Untuk Siswa Kelas I Sekolah Dasar Laboratorium UNDIKSHA Singaraja - I Ketut Juni Sugiarsana; I Gede Mahendra Darmawiguna; I Made Agus Wirawan (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2015)
This current study aimed at (1) developing the Learning Film of Rainy Season In Natural Phenomena Theme For First Grade Students of Laboratory Elementary School UNDIKSHA Singaraja; (2) describing the students' responses to the development of the Learning Film of Rainy Season In Natural Phenomena Theme For First Grade Students of Laboratory Elementary School UNDIKSHA Singaraja. The type of the study was Research and Development Study (R & D) with  ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This study involved the students of First Grade Students of Laboratory Elementary School UNDIKSHA Singaraja in academic year 2013/2014. The data are collected by using interviews, questionnaires, and documentation. The data validation of the Learning Film of Rainy Season In Natural Phenomena Theme was collected from the experts’ assessment using questionnaires. The data of the criteria of the Learning Film of Rainy Season In Natural Phenomena Theme were collected from the students’ responses that analyzed by descriptive qualitative. The result of the study showed that the Learning Film of Rainy Season In Natural Phenomena Theme was in very good criteria. This result based on the test from content expert, the test from media experts and students’ responses. In terms of contents contained in the film and the media design or film display, this Learning Film of Rainy Season In Natural Phenomena Theme was in very good criteria. Based on the analysis of 70 students’ responses known that  61 students stated that the Learning Film of Rainy Season In Natural Phenomena Theme was in very good criteria, two students stated that it was in good criteria, one student stated that it was in quite good criteria, one student stated that it was in not good criteria, and 5 students stated that it was in not very good criteria. The conclusion were the Learning Film of Rainy Season In Natural Phenomena Theme For First Grade Students of Laboratory Elementary School UNDIKSHA Singaraja was developed successfully, and the students' responses to the Learning Film of Rainy Season In Natural Phenomena Theme For First Grade Students of Laboratory Elementary School UNDIKSHA Singaraja was described successfully too.